Responsible Access to Data in International Field Research: A Case Study from Tanzania - Sheikheldin, Gussai H (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2018)
This case study illustrates the author's narrative of his experience obtaining local research ethics approval in Tanzania. It highlights the additional requirements a foreign researcher in Tanzania can encounter with visa approval which is a separate process from research ethics approval. While fulfilling the visa requirements may not be directly related to the ethical administration of research per se, it is part of the responsible conduct of research (RCR) which, among others, includes respect for the local laws and procedures of the host country. The narrative shows that a responsible access to field data in such cases requires fulfilling two separate but complimentary processes: local research ethics review and proper visa attainment. Further, an example of an 'irresponsible' access to data is also presented for comparison and examination of the consequences.